2014
DOI: 10.1128/jcm.00065-14
|View full text |Cite|
|
Sign up to set email alerts
|

Rolling Circle Amplification for Direct Detection of rpoB Gene Mutations in Mycobacterium tuberculosis Isolates from Clinical Specimens

Abstract: e Rapid and accurate detection of multidrug resistance (MDR) in Mycobacterium tuberculosis is essential to improve treatment outcomes and reduce global transmission but remains a challenge. Rifampin (RIF) resistance is a reliable marker of MDR tuberculosis (TB) since by far the majority of RIF-resistant strains are also isoniazid (INH) resistant. We have developed a rapid, sensitive, and specific method for detecting the most common mutations associated with RIF resistance, in the RIF resistance determining re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The combination of padlock-probe circularization and amplification through RCA has proven useful for sensitive and specific detection of nucleic-acid sequences from pathogens (Zhang et al, 1998 ). RCA has gained much popularity in the identification of viral (Haible et al, 2006 ) and bacterial pathogens (Chen et al, 2014 ). Despite its limited use in mycological diagnosis, several studies have demonstrated the applicability of RCA for the molecular identification of medically relevant fungi such as Candida (Zhou et al, 2008 ), Aspergillus (Zhou et al, 2008 ), Trichophyton (Kong et al, 2008 ), Fonsecaea (Najafzadeh et al, 2011 ), Madurella (Ahmed et al, 2014 ), and Mucorales (Dolatabadi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of padlock-probe circularization and amplification through RCA has proven useful for sensitive and specific detection of nucleic-acid sequences from pathogens (Zhang et al, 1998 ). RCA has gained much popularity in the identification of viral (Haible et al, 2006 ) and bacterial pathogens (Chen et al, 2014 ). Despite its limited use in mycological diagnosis, several studies have demonstrated the applicability of RCA for the molecular identification of medically relevant fungi such as Candida (Zhou et al, 2008 ), Aspergillus (Zhou et al, 2008 ), Trichophyton (Kong et al, 2008 ), Fonsecaea (Najafzadeh et al, 2011 ), Madurella (Ahmed et al, 2014 ), and Mucorales (Dolatabadi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The circular structured molecule then amplifies with DNA polymerase that has strand displacement and progressive DNA synthesis activity resulting in series of repeats of the original circular template [11] , [12] . The technique has been proven to be rapid, specific and low-cost for molecular identification of viruses, bacteria, and fungi [13] , [14] , [15] , [16] . It has been applied for identification of a rare black grain mycetoma species Exophiala jeanselmei [17] .…”
Section: Introductionmentioning
confidence: 99%
“…This approach can detect gene mutations associated with drug resistance by using the oligonucleotide probe, which is characteristic of mutation discrimination capability. Such probes used in the previously reported assays include the molecular beacon [ 13 , 14 ], the TaqMan minor groove binder (MGB) probe [ 15 ], the sloppy molecular beacon[ 10 ], the dual-labeled probe[ 16 , 17 ], and the padlock probe[ 18 ] and others. However, none of these probes exhibit rigid specificity to discriminate single-base mutations in the RRDR of M .…”
Section: Introductionmentioning
confidence: 99%
“…The sloppy molecular beacon-based and dual-labelled probe-based approaches need additional Tm analyses after the amplification[ 19 ]. Padlock probes were used in the rolling circle amplifications, which required complex procedure [ 18 ]. In addition to above probes, LNA probe is another kind of probe that has been widely used in real-time PCR to quantitatively detect pathogens [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%